The reproductive strategy in a Chloris virgata population in response to precipitation regimes - Wang Ying; Wang Chunxia; Zhang Jukui; Wang Chunqing (Royal Society Open Science, 2018)
Resource availability influences plant growth and reproduction. Here, a controlled experiment was conducted in order to evaluate the adaptation response of Chloris virgata to different precipitation conditions, and to further predict the reproductive strategy in a population of C. virgata under different precipitation regimes. Three regimes (low, typical and high) of water addition were used to simulate current precipitation patterns. In total 20 individuals for each treatment were analysed to compare tiller number, spike traits, seed traits, the relationship between seed size and seed number, and so on. In addition, the effects of different precipitation regimes on offspring vigour of C. virgata were also studied. Results indicated that tiller number, spike number, seed yield and seed number were unchanged under different water addition regimes, while seed size was about 0.5 mg at typical and high precipitation levels and was higher than that in the low precipitation level. The higher seed mass per spike and spike mass both occurred at typical and high precipitation levels. Significant positive correlations between seed mass and non-seed mass in C. virgata in response to precipitation regimes were largely allometric (size dependent), as was a significant negative correlation between seed size and seed number at low precipitation. The highest germination rates and seedling weights both occurred at typical and high precipitation levels. These findings showed that different precipitation regimes affected reproductive strategy of C. virgata. Chloris virgata will not benefit from low precipitation, while typical and high precipitation will improve seed traits and offspring vigour of this species.